Development Of Solid State Fermentation System For Enzyme Production And Its Usage In A Pilot Scale Deinking Of Printed Waste Paper - Lee, Chee Keong (2010)

(untitled)
The present work deals with the development of solid state fermenter for enzymes production and the development of a pilot scale of enzymatic deinking system. The newly developed solid state fermenter, was named FERMSOSTAT®, which was used for the production of cellulases and xylanase using a local isolate; Aspergillus niger USM AI 1. Kajian ini memberi tumpuan kepada pembangunan fermenter keadaan pepejal untuk penghasilan enzim dan pembangunan sistem penyahdakwatan secara enzimatik berskala rintis. Fermenter yang bam dibangunkan itu dikenali sebagai FERMSOSTAT®.